Cardiac Morbidity Following Chemoradiation in Stage III Non-small Cell Lung Cancer Patients: A Population-Based Cohort Study. Issue 2 (February 2023) - Donovan, E.K.; Pond, G.R.; Seow, H.; Ellis, P.M.; Swaminath, A.
Abstract: Aims: To assess the risk of cardiac toxicity following radical radiotherapy in advanced lung cancer patients. Materials and methods: Patients with a diagnosis of stage III non-small cell lung cancer (NSCLC) receiving chemoradiotherapy were extracted from a population-based cohort in Ontario, Canada. The primary outcome of cardiac toxicity, defined as cardiac events or congestive heart failure, was assessed at 1 and 5 years following chemoradiotherapy. Secondary outcomes included overall survival, survival in relationship to post-treatment cardiac events and the effect of radiotherapy technique on cardiac toxicity. Results: In total, 2031 NSCLC patients were included. The cumulative incidence of cardiac toxicity at 5 years was 20.3% (18.4–22.3). The median survival was 13.7 months in NSCLC patients who had a cardiac event post-chemoradiotherapy compared with 23.4 months in those who did not ( P = 0.012). There was a trend towards increased cumulative cardiac toxicity (hazard ratio 3.37, P = 0.14) with three-dimensional conformal radiotherapy compared with intensity-modulated or volumetric arc radiotherapy techniques. Conclusion: The risk of cardiac events and congestive heart failure 5 years after radical thoracic radiotherapy appears high and survival is inferior at 1 year in those patients who experience a cardiac event post-treatment. More conformal radiotherapy techniques may help reduce cardiac toxicity. Further studies should investigate adaptive treatment planning and close monitoring and intervention in this high-risk group after chemoradiotherapy. Highlights: There may be an elevated risk of cardiac disease following radiotherapy for NSCLC. The risk of death may be higher in patients who experience cardiac events after treatment for NSCLC. Increasing age and male sex may also confer increased cardiac disease risk in NSCLC patients. Treatment technique may have the potential to modify cardiac risk.